Sustainability Issues in River Tourism: A Case Study of Ganges in Varanasi - Tandon, Neha (Atna Journal of Tourism Studies, 2012)
Understanding future expectations and fulfilling current demands with a view of conserving social, cultural and natural environment of a destination, can be referred to as sustainable tourism. Changes in social and cultural environment are identified a little early than their natural counterpart. The first two being more vocal and narrates quick reactions among its audiences. Changes in natural environment lie silent till the time they reach a visible level of depletion. The present paper will highlight sustainability issues in river tourism, which is one of the significant natural resources for tourism. Understanding the dependency of tourism on rivers and highlighting its positive and negative effects of it, will be discussed in the paper. The paper is supported by a case study on „The Ganges in Varanasi‟. The Holy Ganges is the lifeline of the city and is facing immense sustainability issues, which has raised questions against her future existence. The problems faced and measures taken by various organizations, government bodies, and individuals to protect the lifeline of the oldest living city of the world will be examined further.